Spatial Planning Politics in Determining the Location for the Construction of a Waste-To-Energy Power Plant (PLTSa) in Makassar City, Indonesia - Muh Fichriyadi Hastira; Andi Marwah Hermansyah; Gustiana Kambo; Budiman Budiman; Jauchar Barlian; Widya Astuti (Universitas Katolik Indonesia Atma Jaya, 2025)
This research analyzes the political dynamics in determining the location for the construction of a Waste-to-Energy Power Plant (PLTSa) in Makassar City. Although existing regulations, such as Makassar Mayor Regulation No. 1 of 2021 and Makassar City Regional Regulation No. 4 of 2015, have designated the Tamangapa Landfill as the construction site, the city government instead proposed an alternative location in the Tamalanrea District. This has sparked controversy among the community, the Regional People's Representative Council (DPRD), and business actors, as well as causing conflicts of interest among various stakeholders. With a descriptive qualitative approach, this research reveals that spatial planning decisions are not only influenced by technical and environmental aspects but also by political and economic considerations. The shifting of development locations reflects the contestation of power in urban spatial governance, where the interests of political elites and investors are often prioritized over the aspirations of the community. This research highlights the importance of transparency and public participation in spatial planning to avoid social conflicts and ensure spatial justice in infrastructure development policies.